Problematika Kewenangan Pemberian Izin Investasi antara Pemerintah Pusat dan Pemerintah Daerah Pasca Berlakunya Undang-Undang Cipta Kerja - Kadek Nadya Pramita Sari; Anak Agung Gede Ananta Wijaya Sahadewa (Fakultas Hukum, Universitas Warmadewa, 2025)
Law number 11 of 2020 on Job Creation brings fundamental changes in the division of authority between the Central Gorvernment and Regional Governments, especially in terms of granting investment lincences. Through the Omnibus Law approach, this law aims to simplify regulations to improve the investment climate, but simultaneously result in the centralization of authority that was previously in the hands of local governments. This study aims to analyze the impact of this shift in authority on the principle of regional autonomy as stipulated in the 1945 Constitution and the Region Government Law. The method used is normative legal research with a legislative and descriptive-analytical approach. The results show that the authority of local governments in granting investment licences has been significantly restricted, both substantively, due to new provisions in the Job Creation Law and its implementing regulations. This centralization has implications for the potential erosion of regional independence, creates legal uncercainty and obscures the principles of decentralization. These fingdings emphasize the need to strengthen derivative regulations that ensure balanced coordination between the center and regions, to ensure that investment continues without compromising regional autonomy.